The Statistical Approach for Overcoming the Sensor Saturation Effect in Passive Ranging - Mitrović, S. T.; Bondžulić, B. P.; Andrić, M. S.; Barbarić, Ž. P. (Elektronika ir Elektrotechnika, 2014)
Grey level intensity distribution on thermal infrared images is estimated in this research. General Pareto distribution describes grey level distribution better than other considered statistics. Error of passive ranging distance estimation based on intensity method is too large at short distance, because grey level of imaging sensor is saturated. Suggested modification has a great application in compensation of the effect of sensor saturation. Experiment on real saturated infrared sequence demonstrates that distance estimation error of suggested approach increases around three times slower compared to the conventional intensity based approach. DOI: http://dx.doi.org/10.5755/j01.eee.20.2.3788